United States : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2001)
This Selected Issues paper analyzes the condition of household, corporate, and bank balance sheets; sustainability of the U.S. external current account deficit; the impact of a slowdown in the growth on the euro area economy; and the implications of the reduction in U.S. treasury securities for monetary policy and financial markets. The study discusses the pros and cons of investing government assets in private securities; the recent changes in agricultural support policy and their impact on other countries; technological innovations and the adoption of new technologies.